Networked Organizational Structure of Enterprise Information Security Management Based on Digital Transformation and Genetic Algorithm - Di, Zhenpeng; Liu, Yun; Li, Shimei (Frontiers in Public Health, 2022)
With the rapid development of society and economy, enterprises have also started digital transformation in order to follow the pace. Now-a-days, the development of enterprises is also faced with the risk of improper management of enterprise information security, so it is very necessary to study the networked organizational structure of enterprise information security management. The purpose of this paper is to study how to analyze the network organization structure of enterprise information security management based on genetic algorithm. This paper puts forward the difficult problems faced by enterprise information security, and how to prevent and solve the risks encountered in information security. In the experimental part of this paper, it can be seen that with the increase of the number of experiments, the work efficiency of the traditional network organization structure has increased from about 4.6 to about 17%. The work efficiency of the network organization structure based on genetic algorithm has risen from about 10 to about 50%. It shows that the work efficiency of the network organization structure based on genetic algorithm is much higher than that of the traditional network organization structure. It can be seen that the advantage percentage of enterprise information security management networked organizational structure with strong room for growth is 79–84%, and the percentage of cost savings is 75–82%. It can be seen that there are still many advantages of the networked organizational structure of enterprise information security management. The network organization structure based on genetic algorithm can not only improve the work efficiency of enterprises, but also improve the information security. Therefore, the network organization structure based on genetic algorithm is of great significance to the enterprise information security.